2021
DOI: 10.1080/14756366.2021.1959571
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationship, in vitro and in vivo evaluation of novel dienyl sulphonyl fluorides as selective BuChE inhibitors for the treatment of Alzheimer's disease

Abstract: To discover novel scaffolds as leads against dementia, a series of δ-aryl-1,3-dienesulfonyl fluorides with α-halo, α-aryl and α-alkynyl were assayed for ChE inhibitory activity, in which compound A10 was identified as a selective BuChE inhibitor (IC 50 = 0.021 μM for eqBChE, 3.62 μM for hBuChE). SAR of BuChE inhibition showed: (i) o - > m - > p -; –OCH 3 > –CH 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Recently, new aliphatic sulphonyl fluorides containing a triazole moiety were efficiently synthesised through the region-selective cycloaddition reaction of but-3-ene-1,3-disulfonyl difluoride and organic azides 19 . Primary screening of compounds T1–T17 ( Scheme 1 ) was performed with equine BuChE (eqBuChE) and electrophorus electricus AChE (eeAChE) using modified Ellman’s method 20 . As shown in Supplementary Table S1 and Figure 2(A) , all of compounds T1–T17 exhibited inhibitory activity against AChE and BuChE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, new aliphatic sulphonyl fluorides containing a triazole moiety were efficiently synthesised through the region-selective cycloaddition reaction of but-3-ene-1,3-disulfonyl difluoride and organic azides 19 . Primary screening of compounds T1–T17 ( Scheme 1 ) was performed with equine BuChE (eqBuChE) and electrophorus electricus AChE (eeAChE) using modified Ellman’s method 20 . As shown in Supplementary Table S1 and Figure 2(A) , all of compounds T1–T17 exhibited inhibitory activity against AChE and BuChE.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction products were directly screened for eqBuChE and ee AChE inhibitory activity using modified Ellman’s method 20 . Scatter plots of the screening results showed that the compounds had better AChE inhibitory activity, and quinolyl triazolyl sulfonylfluoride ( T14 ) was more potent than phenyl triazolyl sulfonylfluorides ( T2 , T3, and T11 ) in Figure 4(A and B) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1-Bromo-or 1-iodovinyl sulfonyl fluorides were also introduced into Suzuki [80,[121][122][123][124] and Sonogashira [80,121,123] reactions that did not affect the SO 2 F moiety (Scheme 15, A). For the parent vinyl sulfonyl fluoride 7, a possibility of Heck reactions, [80,125,126] oxidative Heck-type reactions with arylboronic acids (Scheme 15, B), [127,128] or palladium-catalyzed CÀ H bond activation in aromatic [125,[129][130][131][132] and aliphatic [133] systems was demonstrated (Scheme 15, C).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, base-mediated intra- [26] and intermolecular [152][153][154][155] alkylations (Scheme 18), as well as Knoevenagel-type condensations with aromatic aldehydes providing styryl [156] or α-halostyryl [121,123,157] sulfonyl fluorides should be mentioned (Scheme 19).…”
Section: Methodsmentioning
confidence: 99%